Submicroscopic placental infection by non-falciparum Plasmodium spp - Doritchamou, J.Y.A.; Akuffo, R.A.; Moussiliou, A.; Luty, A.J.F.; Massougbodji, A.; Deloron, P.; Tuikue Ndam, N.G. (PLoS Neglected Tropical Diseases, 2018)
Background: Among the Plasmodium species that infect humans, adverse effects of P. falciparum and P. vivax have been extensively studied and reported with respect to poor outcomes particularly in first time mothers and in pregnant women living in areas with unstable malaria transmission. Although, other non-falciparum malaria infections during pregnancy have sometimes been reported, little is known about the dynamics of these infections during pregnancy. Methods and findings: Using a quantitative PCR approach, blood samples collected from Beninese pregnant women during the first antenatal visit (ANV) and at delivery including placental blood were screened for Plasmodium spp. Risk factors associated with Plasmodium spp. infection during pregnancy were assessed as well as the relationships with pregnancy outcomes. P. falciparum was the most prevalent Plasmodium species detected during pregnancy, irrespective either of parity, of age or of season during which the infection occurred. Although no P. vivax infections were detected in this cohort, P. malariae (9.2%) and P. ovale (5.8%) infections were observed in samples collected during the first ANV. These non-falciparum infections were also detected in maternal peripheral blood (1.3% for P. malariae and 1.2% for P. ovale) at delivery. Importantly, higher prevalence of P. malariae (5.5%) was observed in placental than peripheral blood while that of P. ovale was similar (1.8% in placental blood). Among the non-falciparum infected pregnant women with paired peripheral and placental samples, P. malariae infections in the placental blood was significantly higher than in the peripheral blood, suggesting a possible affinity of P. malariae for the placenta. However, no assoctiation of non-falciparum infections and the pregnancy outcomes was observed Conclusions: Overall this study provided insights into the molecular epidemiology of Plasmodium spp. infection during pregnancy, indicating placental infection by non-falciparum Plasmodium and the lack of association of these infections with adverse pregnancy outcomes. © 2018 Public Library of Science. All Rights Reserved.